International law and the challenge of climate refugee resettlement - Sarah Salah Hadi; Suad Ahmed Ibrahim; aad Ta’ma Awad Bajjay; Wafaa Adnan Sajid; Ahmed Sabah; Petro Vorona (Environment and Social Psychology, 2025)
While climate change is increasingly acknowledged as a driver of displacement, international legal frameworks have not adequately responded to this emerging phenomenon. Climate-related events displace an estimated 21.5 million people per year, yet no existing international refugee law addresses climate-induced migration, leaving affected populations vulnerable and unprotected. The study examines the legal, economic, and social issues related to climate refugee resettlement. It assesses existing international and regional frameworks, examines dynamics that influence State commitments to resettlement, and positions a new Legal-Resettlement Index (LRI) model. The article includes a comparative legal review, case studies of two high-risk regions, thematic coding of twenty-nine expert interviews, and quantitative modeling of climate migration trends. We apply LRI model to rank countries based on dimensions including legal recognition, economic capacity and climate risk exposure. The results show that high-emission nations tend to have lower resettlement pledges, even while emitting more than 70% of global greenhouse gases. Regional arrangements, while useful, are inadequately enforced (with full recognition in only 32% of cases). Such are processed in a timelier manner; legal reforms and increased funding allocations improve recognition rates by up to 40% and reduce processing times by an average of 15 days. The LRI model shows how its use can identify inequalities and inform policy making. A legally binding Climate Refugee Convention is also crucial for international governance. The are need in stronger regional agreements, and need states with the highest emissions to take disproportionate responsibility. It will also need continued efforts to incorporate climate displacement protections into existing human rights frameworks, and guaranteed, equitable funding mechanisms to deliver sustainable resettlement solutions.